IMPLEMENTASI MODEL PEMBELAJARAN MEDIA VISUAL TERINTEGRASI GAME EDUKATIF GUNA MENINGKATKAN KEAKTIFAN BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI, MATEMATIKA, PKN, EKONOMI DAN PKO - Andi Tabrani Rasyid; Apni Anisa Putri; Elsa Safitri; Eril Fitrah Ramadan; Reva Nabila; Faura Fadila; Ani Sapitri; Nur Jannah; Hikma Fadilah Ramadani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of visual media integrated with educational games to improve student learning activeness in Biology, Mathematics, Civics Education (PKn), Economics, and Physical Education (PKO). The study was motivated by the low level of student participation in learning activities caused by monotonous teaching methods and limited use of interactive learning media. This research employed a quantitative approach using a quasi-experimental design involving experimental and control classes. Data were collected through observation sheets, documentation, and questionnaires regarding student activeness during the learning process. The findings indicate that the implementation of visual media integrated with educational games significantly increased student activeness, participation, collaboration, and responsiveness during classroom activities. Students became more motivated and actively involved in discussions, problem-solving activities, and game-based evaluations. Furthermore, the integration of visual and game-based learning created a more engaging and student-centered learning environment. Therefore, the implementation of integrated visual media and educational games can b considered an innovative learning strategy to improve student activeness across various subjects.